Two cases of bat pollination in Central America - Barker, Herbert G. (Revista de Biología Tropical, 1969)
Visits by bats of the family ,Phyllostomatidae (in the suborder Microchiroptera) to the flowers of Durio zibethinus growing in Honduras and Mucuna andreana growing in Costa Rica are described and illustrated photographically. In Durio we have a case of flower-type which evolved in relation to visits from Megachiroptera in the Old World proving attractive to Microchiroptera which developed the flower-visiting habit in the New World. Hawkmoths also visit these flowers. Both kinds of visitor are capable of causing cross-pollínation (which is necessary for fruit production by this species because it appears to be self-incompatible) . In Mucuna andreana, a native American vine demons trates a close adaptation to pollination by native bats; again a parallel to similar evolutionary development in the Old World.